2023
DOI: 10.3390/toxins15070453
|View full text |Cite
|
Sign up to set email alerts
|

Ciguatera Fish Poisoning in the Caribbean Sea and Atlantic Ocean: Reconciling the Multiplicity of Ciguatoxins and Analytical Chemistry Approach for Public Health Safety

Abstract: Ciguatera is a major circumtropical poisoning caused by the consumption of marine fish and invertebrates contaminated with ciguatoxins (CTXs): neurotoxins produced by endemic and benthic dinoflagellates which are biotransformed in the fish food-web. We provide a history of ciguatera research conducted over the past 70 years on ciguatoxins from the Pacific Ocean (P-CTXs) and Caribbean Sea (C-CTXs) and describe their main chemical, biochemical, and toxicological properties. Currently, there is no official method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 194 publications
(748 reference statements)
0
5
0
Order By: Relevance
“…Neurological and toxicity symptoms of NST are paralysis, seizures, paresthesia, and coma, while gastrointestinal ailments are represented by nausea, diarrhea, vomiting, cramps, and bronchoconstriction, and extreme poisoning may also lead to death . Ciguatera fish poisoning (CFT) is one of the most common foodborne illnesses caused by marine biotoxin of ciguatoxin. , Ciguatoxins are toxic and lipid-soluble compounds found in marine organisms. Gambiertoxins, the precursor toxins, are produced by benthic dinoflagellates of Gambierdiscus genus.…”
Section: Recent Advancements In Food Toxin Detection Using Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurological and toxicity symptoms of NST are paralysis, seizures, paresthesia, and coma, while gastrointestinal ailments are represented by nausea, diarrhea, vomiting, cramps, and bronchoconstriction, and extreme poisoning may also lead to death . Ciguatera fish poisoning (CFT) is one of the most common foodborne illnesses caused by marine biotoxin of ciguatoxin. , Ciguatoxins are toxic and lipid-soluble compounds found in marine organisms. Gambiertoxins, the precursor toxins, are produced by benthic dinoflagellates of Gambierdiscus genus.…”
Section: Recent Advancements In Food Toxin Detection Using Msmentioning
confidence: 99%
“… 161 Ciguatera fish poisoning (CFT) is one of the most common foodborne illnesses caused by marine biotoxin of ciguatoxin. 173 , 174 Ciguatoxins are toxic and lipid-soluble compounds found in marine organisms. Gambiertoxins, the precursor toxins, are produced by benthic dinoflagellates of Gambierdiscus genus.…”
Section: Recent Advancements In Food Toxin Detection Using Msmentioning
confidence: 99%
“…A study feeding omnivorous pinfish with toxic flesh of fieldcollected barracuda found that pinfish retained 43% of consumed C-CTX1 over 20 days [59]. Although they are known to have similar backbone structures, it is unknown how the toxicokinetics may vary among the well-characterized Pacific CTXs and the much lesser known Caribbean CTXs [87]. Additionally, the toxin CTX profile of carnivorous fish contains metabolized and generally more oxidized congeners than that of Gambierdiscus [20,39], which may be assimilated at different efficiencies.…”
Section: Toxin Tissue Burdenmentioning
confidence: 99%
“…Finally, advances are needed in screening methods for the fast detection of toxicity in seafood as well as sensitive and selective targeted analytical methods for the accurate determination of Caribbean ciguatoxin contents [68]. The development of biosensors for the detection of toxic Gambierdiscus and/or Fukuyoa dinoflagellate species and toxic fish specimens is of high value for remote islands, such as the Selvagens Islands.…”
Section: Perspectivesmentioning
confidence: 99%